2003
DOI: 10.1258/135763303322225508
|View full text |Cite
|
Sign up to set email alerts
|

Two-year evaluation of telepathology

Abstract: We evaluated a dynamic telepathology system in routine use after a two-year developmental phase. In two three-month studies, two years apart, all intraoperative frozen sections were examined by one pathologist via the telepathology system. Laboratory technicians sampled tissues at gross examination and were connected with the pathologist by videoconference. Specimens were immediately reviewed after the telepathology diagnosis by the same diagnostician. In the second study there were 342 cases. The mean time re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…In the present study, light microscopy and telemicroscopy agreed in 97.9% of cases; in former studies, the accuracy of telepathology diagnosis with our system and light microscopy was nearly 100%. 3 An accuracy of 97.9% is comparable to the results of other studies, which range from 92% to 100%. 1,8,9 We are not aware of previous inter-observer studies, which show how and/or how intensively diagnosticians trained in telepathology before using such a system.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, light microscopy and telemicroscopy agreed in 97.9% of cases; in former studies, the accuracy of telepathology diagnosis with our system and light microscopy was nearly 100%. 3 An accuracy of 97.9% is comparable to the results of other studies, which range from 92% to 100%. 1,8,9 We are not aware of previous inter-observer studies, which show how and/or how intensively diagnosticians trained in telepathology before using such a system.…”
Section: Discussionsupporting
confidence: 84%
“…Scanning large areas on these smears and/ or on frozen section slides was the weakest part of the robotic microscope during this and in earlier studies. 3 Cases that lasted longer than 40 min mainly fell into this category. Gross examination (3.0 min), time for staining and cutting, plus two smears (6.0 min  2) and three frozen section slides (10.7 min  3) could easily exceed 45 min.…”
Section: Discussionmentioning
confidence: 99%
“…TP was first used for primary frozen section diagnosis in 1989 in Norway [9], where videotelemicroscopy was used to provide intraoperative coverage with 100% accuracy to 5 remote hospitals. In spite of the success of the Norwegian program and others that have followed [7,[10][11][12][13][14][15][16][17][18], the pathology community as a whole has been slow to adopt this technology.…”
Section: Introductionmentioning
confidence: 99%
“…The latter concern persists in spite of the existence of several retrospective validation studies demonstrating an average accuracy rate of 95% (range, 84.1%-100%) [20][21][22][23][24] (Table 1) for TP frozen section diagnoses. Furthermore, there have been at least 11 reports published between 1991 and 2007 showing an average diagnostic accuracy of 96% (range, 89%-100%) when TP was used for primary frozen section diagnosis [7,[10][11][12][13][14][15][16][17][18] (Table 2). With the exception of a few outliers [10,11,22], most articles have reported diagnostic accuracy values that fall within the accuracy range for frozen sections reported by conventional light microscopy [25].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Most studies focusing on intraoperative and fine needle aspiration consultations have shown that the accuracy of telepathology is comparable to conventional in-house methods, though the time required for such diagnoses is usually longer and the deferral rate is sometimes slightly higher. [12][13][14][15][16][17][18][19][20][21][22][23] This technology is particularly useful in certain settings, including transplant pathology, dermatopathology, and neuropathology, where the cases handled are often fundamentally different from general surgical pathology and where on-site subspecialtytrained pathologists are scarce. 20,[24][25][26][27][28][29][30][31][32] Most of the early systems delivered a series of static images over a dedicated ISDN (Integrated Services Digital Network) connection or the Internet, and were shown to be adequate for routine use.…”
Section: Introductionmentioning
confidence: 99%